Supporting incarcerated mothers: a mixed methods evaluation of the NSW Co-Located Caseworker Program - Gibson, Althea (Trends & issues in crime and criminal justice, 2025)
The NSW Co-Located Caseworker Program was established to support women in custody who have children involved in the child protection system. Under the program, child protection caseworkers are ‘co-located’ in NSW correctional centres. We undertook a mixed-methods evaluation of the program by analysing data from Corrective Service NSW’s Offender Integrated Management System and conducting 48 semi-structured interviews with stakeholders, including 25 women in custody. We concluded that the program is a well designed and much needed initiative of benefit to women in custody and their children. However, it could be improved by more coordinated case planning between Corrective Services NSW and child protection services and the increased availability of programs to help women in custody achieve their child protection related goals.